Sufi Politics, A Study of the Activities and Political Thought of the Khalwatiyah Samman Order - Mutakabbir, Abdul (Proceedings of International Conference on Muslim Society and Thought, 2024)
This essay aims to delve into the activities and political ideology of the Khalwatiyah Samman Sufi order. Politics and Sufism are akin to contrasting poles: while politics navigates the affairs of the state and the intricate world, Sufism gravitates towards the afterlife, often disregarding worldly matters, particularly politics. Employing a mixed-method approach, this study incorporates literature review and interviews. Interviews were conducted with the successors of the order’s leadership, two members involved in practical politics, and two participating members. Documentation was utilized, as certain fundamental and significant documents regarding the order remain unpublished, necessitating reference to ensure the research’s comprehensiveness. As for the findings, the Khalwatiyah Samman Sufi order regards the world as a realm for deeds towards the afterlife; thus, it should not be shunned but rather utilized for deeds as much as possible. Similarly, in politics, which lacks inherent orientation, the morality of politics hinges on the politicians; hence, virtuous individuals must engage to uphold ethical standards. The political trajectory of the Khalwatiyah Samman order has a rich history, commencing from its initial congregation of seven individuals in South Sulawesi, three of whom ascended to kingship?namely, the 28th king of Bone, the 33rd king of Gowa, and the 44th king of Wajo. During the Oerde Baru era, one successor of the order assumed membership in the honor council in South Sulawesi. Post-reformation, numerous order members assumed roles in regional and central representative councils, as well as leadership positions such as regents and mayors. According to the Khalwatiyah Samman order, politics is perceived as a tool for drawing closer to God by serving the community indiscriminately, characterized by honesty and trustworthiness. Therefore, politics represents a realm of merit for achieving success in both this world and the hereafter.